(untitled) (Journal of the College of Basic Education, 2019)
Let R be a prime ring and U be a (σ,τ)-left Jordan ideal .Then in this paper, we proved the following , if aU Z (Ua Z), a R, then a = 0 or U Z. If aU C s,t (Ua C s,t), a R, then either a = 0 or U Z. If 0 ≠ [U,U] s,t .Then U Z. If 0≠[U,U] s,t C s,t, then U Z .Also, we checked the converse some of these theorems and showed that are not true, so we give an example for them.